FISIKA ATOM SEBAGAI BASIS FILOSOFIS ILMU DALAM PERSPEKTIF AL-GHAZALI - Imron Mustofa (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2017)
Diskusi tentang atom tidak selalu berbicara ilmu fisika modern. Al-Ghazali seorang filsuf Muslim pada abad ke-12 silam telah jauh mendalami hal ini. Bahkan, atom dijadikannya sebagai konsep dasar ilmu hakiki yang mampu menyingkap hakikat objek pengetahuan, yang pada zamannya mampu menggoncang kemapanan hegemoni filsafat Helenisme di dunia Islam. Secara konseptual, hakikat atom hanya ada dalam pikiran karenanya wujud darinya baru terlihat ketika ada aksiden yang menempel padanya. Implikasi dari itu, akan melahirkan suatu pola pikir yang tidak hanya bersandar pada realita sempiris-rasionalis belaka sebab setidaknya ada lima hierarki realitas yang ada; essential, sensory, imaginal, conceptual dan similar existence. Adanya lima hal itu secara tidak langsung telah mengidentifikasikan lima tingkatan filter bagi “sesuatu” dapat dikatakan logis. Dengan kata lain, apa yang secara esensial (objektif) benar belum tentu dapat diterima kebenarannya melalui perspektif subjektif seseorang. Begitu juga dengan apa yang digambarkan pikiran kita dapat diterima secara konseptual (rasio) ataupun secara empiris.Untuk itu kebenaran yang hakiki bagi al-Ghazali tidak hanya sebatas konseptual ataupun imajinal belaka, namun merupakan suatu kebenaran yang dibimbing wahyu (al-hudūriy), yang mampu mencakup kelima realitas di atas, bukan semata hasil olah pikir (al-husūliy). Hal terakhir ini pulalah yang selama ini menjadi andalan para filsuf Helenisme.The discussion about atom doesn’t always talk about physics. Al-Ghazali as one of Muslim philosopher in past 12 th century has been profound talk about it. Moreover, the atom is being modified as the basic concept of true science, unveils the reality of the object of science. Which in its day has been able to shake up the established hegemony of Greek philosopher on the Islamic world. From the philosophical point of view, what al-Ghazali builds–conceptually, we may assert that he is enthusiastically want to emphasize that the reality of atom “is only in the mind”, hence its physical embodiment is only able to be seen by the presence of “accident” adhere to. Logically, it will cause a way of thinking to occur, not simply be based on empiric-rational reality, but rather on five hierarchy of existences; essential, sensory, imaginal, conceptual and similar existence. Those fives indirectly identify five standards of filter for “thing” can be classified as “logic”. It means the thing which is essentially (objectively) true, in definitively is accepted as so from subjective angle. Indeed, what we think as valid, is unabsolutely will be accepted from conceptual (ratio) and empirical point of view. That’s why, the reality of truth-according to al-Ghazali, is not purely based on the conceptual or imaginal angle, but a divine guided truth (al-hudūriy). It encompasses all those five realities, not only as the product of thought (al-husūliy). In short, what al-Ghazali offers is an integrated point of view, to understand the existing reality, using unseparated way, unites between methods of deductive and inductive, rational and empirical and so on.